Relationship between Ce3+ 5d1 level, conduction-band bottom, and shallow electron trap level in Gd3Ga5O12:Ce and Gd3Al1Ga4O12:Ce crystals studied via pump-probe absorption spectroscopy - Mamoru Kitaura; Heishun Zen; Shinta Watanabe; Hirokazu Masai; Kei Kamada; Kyoung-Jin Kim; Akira Yoshikawa; Jumpei Ueda (Optical Materials: X)
Ce3+-doped compounds are typically the preferred materials for the development of inorganic phosphors for white LEDs, displays, and scintillators. In this study, pump-probe absorption spectroscopy was performed for Gd3Ga5O12:Ce and Gd3Al1Ga4O12:Ce crystals using ultraviolet (UV) and visible (VIS) pump light, and infrared (IR) probe light. A change in the IR-absorption was observed owing to the generation of free carrier plasma via photoexcitation. Through a simple analysis, the excitation spectra of this change determined the energy at the bottom of the conduction band relative to that at the Ce3+ 4f level. The transient response of the IR-absorption change suggested different relaxation processes for excited electrons in Gd3Ga5O12:Ce and Gd3Al1Ga4O12:Ce. Analysis of the thermally stimulated luminescence (TSL) glow curve determined the trap depth of the electrons in Gd3Al1Ga4O12:Ce. Based on positron annihilation lifetime spectroscopy (PALS), the generation of electron traps was linked to the introduction of vacancy complexes or vacancy aggregates with a negative charge, namely nonstoichiometric compositions. This helps achieve high-quality Ce3+-doped multicomponent oxides.